Analisis Lagu 1910 Karya Iwan Fals Dengan Menggunakan Pendekatan Mimetik - Manurung, Parwati (Lembaga Bale Literasi, 2024)
Abstract Literature is self-expression through experiences that have existed in a person's soul through a process of imagination which is then turned into a literary work. One literary work is in the form of a song, be it a national song, pop song, religious song, or regional song. In this case, the type of song being analyzed is a pop song. This research aims to find out and describe the mimetic approach to the 1910 song by Iwan Fals. This mimetic approach views poetry as a representation of nature or a picture of the world and human life in this universe. Through the lyrics of his song, Iwan Fals created this song based on the tragic accident involving two trains in the Pondok Betung area, Bintaro, South Jakarta, on October 19 1987, which was the worst disaster in the history of railways in Indonesia.